Comparison of minimally invasive percutaneous fixation and open reduction internal fixation for patella fractures: a meta-analysis - Chun-Hong Lo; Chih-Hwa Chen (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Open reduction internal fixation (ORIF) has long been the conventional procedure for managing displaced patella fracture. This surgical approach has certain drawbacks, which might affect clinical outcomes and patient prognosis. Minimally invasive percutaneous fixation (MIPF) was proposed to overcome these disadvantages. Few in-depth investigations have been performed to determine the superiority of MIPF over ORIF. The aim of this study was to compare the efficacies of MIPF and ORIF for patella fractures. Methods The PubMed, Cochrane Library, Embase, and Scopus databases were searched for relevant studies from November 26 to December 17, 2020. Non-English publications and pediatric orthopedic articles were excluded. Statistical analysis was performed using Review Manager, version 5.4, with mean differences (MDs), standardized mean differences (SMDs), odds ratios (ORs), and respective 95% confidence intervals (CIs) calculated using a random effects model. The primary outcomes were the pain score, knee range of motion, and joint functionality. The secondary outcomes were the surgical time, complications, and implant removal rate. Results Six articles with a total of 304 patients were included in the meta-analysis. Pooled analysis revealed that patients with MIPF had a significantly reduced pain score (MD = − 1.30, 95% CI = − 1.77 to −0.82; p < 0.00001) and increased knee extension angles (MD = 0.72, 95% CI = 0.18 to 1.25; p = 0.009) at 3-month follow-up. Furthermore, knee flexion angles (MD = 8.96, 95% CI = 5.81 to 12.1; p < 0.00001) and joint functionality (SMD = 0.54, 95% CI = 0.21 to 0.86; p = 0.001) had statistically improved at 2 years. However, no difference was observed between MIPF and ORIF with regard to the surgical time. The risk of complications (OR = 0.10, 95% CI = 0.05 to 0.18; p < 0.00001) and implant removal rate (OR = 0.20, 95% CI = 0.07 to 0.57; p = 0.003) were significantly lower with MIPF than with ORIF. Conclusions MIPF is more favorable than ORIF in terms of the pain score, knee range of motion, joint functionality, complications, and implant removal rate. Thus, it can be adopted as an alternative to ORIF.